#TITLE_ALTERNATIVE# - FALUGON (NIM : 13706003) Tim Pembimbing : Dr. Ir. Aditianto Ramelan; Ir. Numan Basir, GESA
Anodizing is a process for producing decorative and protective films on article made from aluminum and its alloys. Anodizing process produces a passive oxide layer is positioned on a particular metal as the anode. Anodizing can improve surface hardness, corrosion resistance, electrical resistance and the appearance of the surface of the aluminum through dye coloring process. To obtain the optimal oxide layer an optimizing of parameters, such as type and concentration of electrolyte, additive, current density, temperature and processing time should be employed. This research is conducted to find the effect of temperature and varying oxalic acid concentration on hardness and thickness of oxide layer formed on specimen surface which is aluminum 7075. The electrolyte used was a mixture of sulfuric acid and oxalic acid. The H2SO4 was kept constant at 20 w/o and the oxalic acid was varied i.e. 10 g/l, 15 g/l and 20 g/l. Voltage used in the anodizing process was kept constant at 12.5 Volt, with variations electrolyte temperature of 5o C, 10o C and 15o C for 90 minutes. The anodized layer was characterized by Vickers micro-hardness tester and thickness measurement was carried out by using an optical microscope and SEM equipped with an EDAX. It can be concluded that increasing electrolyte temperature will reduce the layer hardness, and the higher concentration of oxalic acid will thicken the oxide layer. At this condition film growth rate will be greater than the dissolution rate by the electrolyte. The maximum hardness and layer thickness of 332 VHN and 44 μm was obtained at 5 0C and 20 g/l of oxalic acid. Lowering anodizing temperature and increasing concentration of oxalic acid will produce higher hardness and thickness up to a certain value. Further research should be undertaken to find more optimized condition.